The myth of giving as good: Charitable giving represented as an end in itself. (October 2018) - Lloyd, Harriet R.
Highlights: Fundraising is celebrated as an end in itself. Giving = good is a Myth (Barthes). Focus group participants orient to the idea outcomes for beneficiaries are important. Abstract: The relationship between viewers and beneficiaries of televised charity fundraising campaigns of various types has been researched and theorised in various ways, perhaps most influentially by Boltanski (1999) and Chouliaraki (e.g. 2006). In this article, I focus on an aspect of this relationship foregrounded by Boltanski: the degree to which viewers are encouraged to consider it possible to take action to prevent the suffering they are presented with. I draw on the concept of myth (Barthes, 2009) in order to study the degree to which fundraising is imbued with additional meanings, while other potential actions are obscured. Importantly, I apply these theories to an under-researched genre of charity communication: the intra-national telethon (in this case, the 2011 edition of the BBC's 'Children in Need'). I complement analysis of this programme with that of a series of focus groups carried out in the fortnight following this broadcast with groups of people who have different professional and voluntary relationships with UK-based charities. I apply Rhetorical Discourse Analysis (Arribas-Ayllon et al., 2013) to the data because of its unique focus on accounts as a pervasive social activity; in both mediated and spoken charity discourse, the request for money and the response (or lack thereof) to such requests requires the constant production of justifications.